Correlation between volume of root canal, cultivable bacteria, bacterial complexes and endotoxins in primary infection - Cardoso, Flávia Goulart da Rosa [UNESP]; Martinho, Frederico Canato [UNESP]; Ferreira, Nádia de Souza [UNESP]; do Prado, Renata Falchete [UNESP]; Manhães-Júnior, Luiz Roberto Coutinho [UNESP]; Rocco, Marco Antônio [UNESP]; Valera, Marcia Carneiro [UNESP] (FapUNIFESP (SciELO), 2019)
This clinical study was conducted to correlate the levels of endotoxins and culturable bacteria found in primary endodontic infection (PEI) with the volume of root canal determined by using Cone Beam Computed Tomography (CBCT); and to evaluate the bacterial diversity correlating with clinical features. Twenty patients with PEI were selected and clinical features were recorded. The volume (mm3) of root canal was determined by CBCT analysis. Root canal samples were analyzed by using kinetic LAL-assay test to determine the levels of endotoxins and anaerobic technique to determine the bacterial count (CFU/mL). DNA was extracted from all samples to determine bacterial diversity and quantified by using Checkerboard-DNA-DNA- Hybridization. Culturable bacteria and endotoxins were detected in 100% of the root canal samples. Linear regression analysis revealed a correlation between root canal volume and presence of anaerobic bacteria (p<0.05). Positive correlations were found between bacteria species and presence of different clinical features (p<0.05). After grouping the bacteria species into bacterial complexes, positive associations were found between green, orange and red complexes with presence of sinus tract (p<0.05). This clinical study revealed that larger root canals hold higher levels of culturable bacteria in PEI. Thus, the interaction of different virulent bacteria species in complexes seems to play an important role in the development of clinical features.
Keywords: Bacteria; Endodontic infection; Endotoxin